Cost-Benefit Analysis for Climate Information Services: Training for County Directors of Meteorological Services (CDMS) - Murage, Paul; Braun, Mélody; Smith Ruiz, Paulina; Mwai, Zacharia; Kimani, Margaret; Kangila, Isaac; Muriuki, Edward; Chemaiyo, Pascaline; Kramer, Berber (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This report summarizes the findings of a 3-day training program for eighteen (18) Kenyan Meteorological Department County Directors of Meteorological Services (CDMS), on Cost Benefit Analysis for Climate Information Services (CBA for CIS), in Nakuru, Kenya on March 12-14th 2025. The program was jointly organized by the “Accelerating Impacts of CGIAR Climate Research for Africa” (AICCRA) program and the Institute for Meteorological Training and Research (IMTR) at the Kenya Meteorological Department (KMD). The training aimed at building the capacity of CDMS to think critically through ways to quantify and evaluate the monetary and non-monetary costs and benefits of the climate information services developed in their counties, with a strong focus on Gender Equity and Social Inclusion (GESI). Training materials built on an online training conducted by IFPRI, AICCRA and the CGIAR Gender Platform in November and December 2024, and were tailored to the CDMS context during a validation workshop held on March 10th and 11th, 2025.